PROBLEM OF THE EVALUATION OF MILITARY ELEMENT COHESION - Borodin, B. D. (Honor and Law, 2019)
In modern conditions, the problem of cohesion of military collectives became particularly relevant. Traditional approaches to the unification of servicemen on the basis of "friendship and fraternity" proved to be ineffective. The events of recent years have shown the existence of fundamental contradictions in the thoughts, views and actions that led to the facts of betrayal and separatist actions. The formulation of a military oath for a certain part of the military and law-enforcement agencies has become a formality. The purpose of the article is to analyze the problem aspects of assessing the unity of military personnel in National Guard of Ukraine military units in accordance with the main areas in which there is interaction between them and the conditions of unification as one of the factors of the morally-psychological state of military personnel and units. The proposed option for assessing the cohesion of military units can be considered as one of the possible tools for periodic use by commanders (without special training) in the short term to obtain sufficiently objective information on changes in one of the essential processes of group dynamics and the existing problems in this area with purpose of timely and adequate response to them. Practical aspects of military men’s cohesion evaluation that characterize the fullness, authenticity and the procedure of obtaining information about the concerted action of military men during the duty tour are considered.